Modification Technology of Surimi Processing through Utilization “By-Catch” of Shrimp Net in Arafura Sea - Nazori Djazuli; Mita Wahyuni; Daniel Monintja; Ari Purbayanto (Jurnal Pengolahan Hasil Perikanan Indonesia, 2009)
Utilization of shrimp net in Arafura Sea produced by–catch with average ratio 1:12 between main capture and by–catch. The low economic value, unavailability of suitable processing technology, and constraint in management by–catch lead to discharge the majority of by-catch to the sea. The aims of this research were to analyze the availibility of raw material of surimi from by–catch of shrimp net in Arafura Sea and modified processing technology from mixture of fish species by prepared minced fish in vessel and surimi processing of mixture fish  species in land and followed by quality assessment of surimi. Result of the research showed that number of 502 vessels operated – mostly by–catch – per vessel unit per year was 795 metric ton, therefore the estimation of volume of by–catch per year in Arafura was 399,000 metric ton. Fish species of by-catch that suitable processed into surimi was 32% or 128 metric  ton/year or equivalent to 41,000 metric ton of surimi per year. Result of cut off technology analysis showed that frozen minced fish could be stored for 5 weeks at –18oC which constantly produced good surimi (folding test: A, teeth cutting test:7 and gel strength > 500 g/cm2). Producing “minced fish” in fishing vessels would decrease weight to 60% and volume fourfold compose to whole fish without decreasing the quality of surimi produced.Keywords : by–catch, minced fish, non economic fish, surimi, quality of surimi.